Perception, awareness and utilization of integrated child development services scheme by mothers in coastal Karnataka, India - S. V., Saranya; Kumar, Ashwini; Kulkarni, Muralidhar M.; Kamath, Asha (International Journal Of Community Medicine And Public Health, 2022)
Background: Integrated Child Development Services (ICDS) scheme is the leading outreach program aimed at promoting maternal and child health care and help in strengthening the implementation of MCH activities like immunization, growth monitoring, supplementation of vitamin A and iron folic acid tablets. Hence, ICDS takes holistic approach in development of children and attempts to improve their prenatal and post-natal environment. Hence the present study was undertaken to study the awareness and utilization of ICDS scheme by expectant mothers and nursing mothers in coastal Karnataka. Objectives of current study were to study the awareness and utilization of services offered to mothers under ICDS 2 and to assess the perception about the services. Methods: A community based cross sectional study was done among 141 mothers registered in anganwadis. Results: Majority were aware of SN (96.5%) followed by TT immunization (89.4%) and NHED (22%). The most common service utilized by the study subjects was supplementary nutrition (94.3%) followed by NHED (24.1%) and home visit (23.4%). Larger proportion of the study subjects were of opinion that SN food of good quality (57.1%) and almost 96.2% mothers said food was of adequate quantity. Conclusions: Among the eligible expectant and nursing mothers, majority of them utilized supplementary nutrition. Nearly 40% of expectant and nursing mothers were not happy about the quality of food offered to them. Nutrition and health education sessions were attended by only 40% of the eligible mothers.